Essential role for hematopoietic prostaglandin D2 synthase in the control of delayed type hypersensitivity - Seema Trivedi; Justine Newson; Ravindra Rajakariar; Thomas S. Jacques; Robert Hannon; Yoshihide Kanaoka; Naomi Eguchi; Paul Colville‐Nash; Derek W. Gilroy (2006)
Hematopoietic prostaglandin D 2 synthase (hPGD 2 S) metabolizes cyclooxygenase-derived prostaglandin (PG) H 2 to PGD 2 , which is dehydrated to cyclopentenone PGs, including 15-deoxy-Δ 12,14 -PGJ 2 (15d-PGJ 2 ). PGD 2 acts through two receptors (DP1 and DP2/CRTH2), whereas 15d-PGJ 2 can activate peroxisome proliferator-activated receptors or inhibit a range of proinflammatory signaling pathways, including NF-κB. Despite eliciting asthmatic and allergic reactions through the generation of PGD 2 , it is not known what role hPGD 2 S plays in T helper (Th)1-driven adaptive immunity. To investigate this question, the severity and duration of a delayed type hypersensitivity reaction was examined in hPGD 2 S knockout and transgenic mice. Compared with their respective controls, knockouts displayed a more severe inflammatory response that failed to resolve, characterized histologically as persistent acute inflammation, whereas transgenic mice had little detectable inflammation. Lymphocytes isolated from inguinal lymph nodes of hPGD 2 S −/− animals showed hyperproliferation and increased IL-2 synthesis effects that were rescued by 15d-PGJ 2 , but not PGD 2 , working through either of its receptors. Crucially, 15d-PGJ 2 exerted its suppressive effects through the inhibition of NF-κB activation and not through peroxisome proliferator-activated receptor signaling. In contrast, lymph node cultures from transgenics proliferated more slowly and synthesized significantly less IL-2 than controls. Therefore, contrary to its role in driving Th2-like responses, this report shows that hPGD 2 S may act as an internal braking signal essential for bringing about the resolution of Th1-driven delayed type hypersensitivity reactions. Consequently, hPGD 2 S-derived cyclopentenone PGs may protect against inflammatory diseases, where T lymphocytes play a pathogenic role, as in rheumatoid arthritis, atopic eczema, and chronic rejection.